Preferences for Biodiversity-Promoting Private Garden Designs: A Basket-Based Choice Experiment - Tobias Börger; Danny Campbell; Jürgen Meyerhoff; Malte Welling (Environmental and Resource Economics, 2026)
This study introduces the basket-based choice experiment (BBCE) as suggested by Caputo and Lusk (2022) into the field of environmental economics and management. The application is a survey to assess garden owners' preferences for installing design elements conducive to biodiversity conservation in private gardens. In addition to showcasing this approach in the context of environmental management, the present application of the BBCE adds two new methodological features to this approach. First, an experimental design is used to provide context attributes for each basket-based choice task to assess the extent to which policy levers set by local councils can affect how garden owners design their gardens. Second, the econometric model to analyse the resulting basket-based choice data is augmented by a latent class structure to accommodate the empirical finding that a substantial share of respondents never chose to add any new element to their gardens (i.e. chose an empty basket). Results show that the policy instruments have mixed effects on the element-specific choice probabilities, with financial support for new garden elements exhibiting the strongest effect on demand. Furthermore, it is demonstrated how prediction can be used to assess the uptake of biodiversity friendly garden elements as a function of policy instruments.
Keywords: D12; Q57; Q58; 330; Biodiversity; Basket-based choice experiment; Private gardens; Policy instruments; Wildlife gardening